Defective Homojunction Porphyrin‐Based Metal‐Organic Frameworks for Highly Efficient Sonodynamic Therapy. Issue 1 (22nd December 2022) - Zeng, Yuxuan; Ouyang, Qunle; Yu, Yi; Tan, Lei; Liu, Xiangmei; Zheng, Yufeng; Wu, Shuilin
Abstract: Sonodynamic therapy (SDT) with non‐invasiveness and high tissue‐penetrating ability has attracted widespread interest in treating deep‐seated tumors or infections. To enhance the treatment efficacy of SDT, the development of high‐efficiency and stable sonosensitizers are still needed. Herein, a defective homojunction porphyrin‐based metal‐organic framework (MOF) with greatly enhanced sonocatalytic ability is easily prepared and used for SDT of osteomyelitis infected by methicillin‐resistant Staphylococcus aureus (MRSA). Acetic acid and benzoic acid are chosen as modulators during the hydrothermal synthesis of porphyrin‐based MOF. It is found that the crystal structure of MOF shifts from PCN‐222 to PCN‐224 as the amount of acetic acid increases. Interestingly, the defective PCN (D‐PCN) contains a two‐phase homojunction structure of PCN‐222/PCN‐224. The sonocatalytic reactive oxygen species production presents a volcano‐type trend with increased acetic acid, among which D‐PCN‐2 with more content of PCN‐224 has the best sonocatalytic antibacterial ability. The reduced band gap introduced a defect, and type‐II homojunction structures of D‐PCN‐2 improve the separation of the ultrasound‐triggered electron hole, which significantly enhances the SDT effect. Through a mixed linker approach, this work develops a new defect‐induced homojunction MOF with great performance for SDT of MRSA‐infected osteomyelitis. Abstract : A two‐phase homojunction porphyrin‐based metal‐organic framework is prepared through acid‐modulated defective engineering. Due to the reduced band gap, introduced defect, and type‐II homojunction structures, the selected PCN‐222/PCN‐224 homojunction (D‐PCN‐2) has the strongest sonocatalytic effect for the efficient treatment for MRSA‐infected osteomyelitis.